Entre testemunhos e documentos: a Comissão Nacional da Verdade e seu legado informacional para a justiça de transição - Ana Cláudia Ribeiro (2022)
The National Truth Commission clarified the serious human rights violations that occurred during the military dictatorship period. To achieve this, it was necessary to recover information that had been omitted, distorted, or denied to society. This thesis aims to understand the contribution of testimonies and documents in the development and formalization of the final report of the National Truth Commission, identifying their role in constructing an informational legacy for transitional justice in Brazil. The intended analysis was based on examining the historical-legal context of testimonies, documents, archives, Transitional Justice, and truth commissions both internationally and in Brazil. The methodology employed was a qualitative-quantitative bibliographic research, based on content analysis of the citations from the final report of the National Truth Commission. Through the creation of an ad hoc database, 7,972 citations were recorded, with a higher incidence of documents, accounting for 89% of the sources of information, compared to the testimonies collected by the Truth Commission, which represented 11% of the total. Due to the volume of citations, five cases were chosen for analysis: Operation Condor, Universities, LGBT, Chael Case, and the Forensic Center. These cases demonstrate the significance of documents over testimonies, potentially linked to the timeframe of the establishment of the Truth Commission, given that it occurred more than thirty years after the end of the military regime, resulting in the appropriation of documentary sources produced externally to the Commission itself. To better understand the analyzed sources of information, the producing institutions were mapped, resulting in the following categories: Truth Commission, Government, Military Regime, Press, International Organization, Non-Governmental International Organization, Civil Society, and University. Regarding the type of information produced by the institutions, normative acts, decrees, laws, official letters, telegrams, opinions, memoranda, reports, oral sources, articles, letters, minutes, military police inquiry reports, books, theses, and films were identified. The research revealed that the more documents recovered about a specific victim, the higher the details associated with the case, such as photos, interrogation records, and the violence committed. The five investigated cases confronted multiple sources from multiple producing institutions. The National 11 Truth Commission leaves an informational legacy for Transitional Justice by gathering, systematizing, and comparing sources of information through verification of authenticity and content. In doing so, it produces new documents, establishing itself as a legitimate and reliable forum to reveal the truth about the violence perpetrated by the regime by the guidelines advocated by international law.